Complex fractures of the humeral shaft treated with antegrade locked intramedullary nail: clinical experience and long-term results - Campochiaro, Gabriele; Baudi, Paolo; Loschi, Roberta; Serafin, F.; Catani, Fabio (Acta Biomedica Atenei Parmensis, 2015)
Background: indications for surgical treatment of complex humeral shaft fractures are still controversial. The purpose of this study was to evaluate the outcomes of treating humeral shaft fractures using antegrade locked  intramedullary nail, compared to the treatment with traditional more aggressive techniques such as plate and screws. Methods: between February 2008 and January 2011 38 patients were treated with antegrade locked intramedullary nail for humeral shaft fractures, divided according to the AO classification. 28 patients were clinically followed: disability, pain and functional recovery were evaluated using the Constant score and DASH score and the ROM of the shoulder was checked. Results: Bony union was obtained in 27 patients at a mean time of 2.7 months. One fracture ended in nonunion, healed after replacing the nail with a longer one. Patients achieved satisfactory shoulder function with a mean Constant score of  90.57 points and with a mean DASH score of 4.69 points. There were no other complications. Conclusion: the antegrade locked intramedullary nail represents a recommended option for the treatment of humeral shaft fractures, obtaining a steady synthesis, a short time of consolidation and a rapid functional recovery. (www.actabiomedica.it)